Modelling the Effect of Copper on the Mo-reduction Rate of the Antarctic Bacterium Pseudomonas sp. strain DRY1 - Rahman, Mohd Fadhil; Ahmad, Siti Aqlima; MacCormack, Walter Patricio; Ruberto, Lucas; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2017)
Molybdenum reduction by the Antarctic bacterium Pseudomonas sp. strain DRY1 is strongly inhibited by copper. Mo reduction by this bacterium at 10 mM sodium molybdate shows a sigmoidal pattern with lag periods ranging from 7 to 10 h at various concentrations of copper. As the concentration of copper was increased, the overall Mo reduction rate was inhibited with 1.2 mg/L causing the cessation of Mo reduction rate. The modified Gompertz model was utilized to obtain Mo reduction rates at different concentrations of copper. The Mo reduction rates obtained from the modified Gompertz model was then modelled according to the modified Han-Levenspiel, Wang, Liu, modified Andrews and the Amor models. Out of the five models, only Wang, modified Han-Levenspiel and the Liu models were able to fit the curve, whilst the modified Andrews and Amor models were unable to fit the curves. Both the Wang and modified Han-Levenspiel models show acceptable fitting while the Liu model shows poor fitting. Results of the statistical analysis showed that the modified Han-Levenspiel model was the best model based on the lowest values for RMSE and AICc, highest adjusted correlation coefficient (adR2) and values of AF and BF closest to unity. The parameters obtained from the modified Han Levenspiel model, which were Ccrit, ïmax and m which represent critical heavy metal ion concentration (mg/l), maximum reduction rate (nmole Mo blue/h) and empirical constant values were 0.225 (95%, confidence interval from 0.198 to 0.251), 1.200 (95%, confidence interval from 1.180 to 1.220) and 0.443 (95%, confidence interval from 0.261 to 0.626). The modified Han-Levenspiel accurately predicted the critical copper concentration that completely inhibited molybdenum reduction rate in this bacterium.